2011
DOI: 10.1590/s1516-80342011000100020
|View full text |Cite
|
Sign up to set email alerts
|

Audiometria de altas frequências no diagnóstico complementar em audiologia: uma revisão da literatura nacional

Abstract: A audiometria de altas frequências (AAF) é um exame audiológico importante na detecção precoce de perdas auditivas por lesões na base do ducto coclear. Nos últimos anos, a sua utilização foi facilitada pelo fato de os audiômetros comercializados passarem a incorporar frequências superiores a 8 kHz. Porém, existem diferenças relacionadas aos equipamentos utilizados, às metodologias empregadas e/ou aos resultados e interpretação. Assim, o objetivo deste artigo foi analisar a produção científica nacional sobre a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
12
0
14
Order By: Relevance
“…Analysis of the auditory sensitivity at high frequencies in 125 adolescents aged 12-17 years with harmful hearing habits (use of MP3 player) demonstrated no correlation between use of MP3 player and auditory thresholds, and a division into 12-14 and 15-17-year age groups showed an increased mean for higher thresholds in the group composed of older individuals for all frequencies tested, except for 11,200 Hz (18) . Although characterization of high-frequency thresholds by age group in adolescence shows worse responses in the older age group (23,24) , there is no agreement on the exact period that this reduction begins (25,26) . Aiming to investigate the hearing thresholds of dentists, dentist's assistants, and dental prosthesis technicians, 108 professionals aged 17-59 years were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the auditory sensitivity at high frequencies in 125 adolescents aged 12-17 years with harmful hearing habits (use of MP3 player) demonstrated no correlation between use of MP3 player and auditory thresholds, and a division into 12-14 and 15-17-year age groups showed an increased mean for higher thresholds in the group composed of older individuals for all frequencies tested, except for 11,200 Hz (18) . Although characterization of high-frequency thresholds by age group in adolescence shows worse responses in the older age group (23,24) , there is no agreement on the exact period that this reduction begins (25,26) . Aiming to investigate the hearing thresholds of dentists, dentist's assistants, and dental prosthesis technicians, 108 professionals aged 17-59 years were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are in disagreement with some other studies that have observed patients submitted or not to antiretroviral treatment and found higher occurrence of conductive hearing loss in the group submitted to treatment (30.8%) when compared to the group without treatment (20%), Chi-square test for homogeneity (p<0.001) Groups were assessed together, except for Control Group, whose results were normal for CPTA and HFA Note: CPTA = Conventional Pure Tone Audiometry; HFA = High Frequency Audiometry; RGI = Research Group I; RGII = Research Group II whose finding was justified by the fact that those who take medication are normally subjects with longer duration of infection and more marked immunosuppression (26) . HFA is a test that has shown great potential for hearing loss early detection because the basal cochlear region, where the hair cells can be found, is the first to be affected by auditory abnormalities caused by endogenous and exogenous factors, enabling the anticipation of potential CPTA affections (27,28) . Auditory monitoring of subjects that take ototoxic medication using HFA has provided early evidence about the maximum limit dose that may cause hearing loss, leading to ototoxicity prevention and reduction of severity.…”
Section: Discussionmentioning
confidence: 99%
“…A DA, geralmente, é resultante de mudanças relacionadas à idade no metabolismo, degeneração do nervo coclear e alterações mecânicas no órgão espiral, com consequentes efeitos adversos sobre a função auditiva periférica e central (Brizzee et al, 1980;Trehub et al, 1989;Schuknecht e Gacek, 1993;Mazelova et al, 2003). Contudo, com o avanço tecnológico e maior conhecimento da relação entre audiologia e física acústica, espera -se que a falta de fidelidade dos padrões de calibração para as frequências ultra-altas possa ser superada devido à aplicabilidade das mesmas, como nos casos de monitoramento de pacientes com presença ou suspeita de patologias relacionadas à audição como ototoxidade, sequela de otite média, presbiacusia, exposição ao ruído e em portadores de insuficiência renal (Zeigelboim et al, 1996;Pialarissi e Gattaz, 1997;Vallejo et al, 2001;Carvallo, 2002;Garcia et al, 2003;Klagenberg et al, 2011). Shaw et al (1996) Para verificar se seria possível identificar uma diminuição nas respostas da função coclear dos pais portadores em heterozigotos da mutação do gene GJB2, o presente estudo adotou uma metodologia eletroacústica que foi capaz de confirmar a hipótese inicial, embora novos estudos sejam necessários à medida que os avanços tecnológicos permitem maior precisão no registro das EOA-PD em frequências ultra-altas.…”
Section: -Análise Dos Resultados Dos Exames De Atl Ra E Eoa-pd Em Frunclassified
“…Dentre elas, merecem destaque: monitorização do efeito de drogas ototóxicas, sequela de otite média, monitorização da audição em portadores de insuficiência renal, presbiacusia, avaliação dos distúrbios de processamento auditivo, monitorização de indivíduos com exposição frequente ao ruído, processos degenerativos do órgão espiral e investigação do comprometimento auditivo em familiares de portadores de DA de origem genética (Zeigelboim et al, 1996;Pialarissi e Gattaz, 1997;Vallejo et al, 2001;Carvallo, 2002;Garcia et al, 2003;Klagenberg et al, 2011).…”
Section: -Avaliação Da Audição Em Frequências Altasunclassified